Discovery and development of ANV419, an IL-2/anti-IL-2 antibody fusion protein with potent CD8+ T and natural killer cell-stimulating capacity for cancer immunotherapy - Patrizia Murer; Barbara Brannetti; Jean-Michel Rondeau; Laetitia Petersen; Nicole Egli; Simone Popp; Catherine Regnier; Kirsten Richter; Andreas Katopodis; Christoph Huber (Taylor & Francis Group, 2024)
Novel engineered IL-2 agonists strive to increase the therapeutic window of aldesleukin (human IL-2) by increasing selectivity toward effector over regulatory T cells and reducing dose-limiting toxicities. Here we describe ANV419, an IL-2/anti-IL2 antibody fusion protein designed for selective IL-2 receptor βγ (IL-2 Rβγ) activation by sterically hindering IL-2 from binding to IL-2 Rα. The fusion protein has an IL-2 connected to the light chain complementarity-determining region (CDR) domain of a humanized antibody that binds to IL-2 at the same epitope as IL-2 Rα. Optimization of the selectivity and pharmacological properties led to the selection of ANV419. ANV419 preferentially expands CD8+ T cells and natural killer (NK) cells over Tregs and can be safely administered at doses that elicit strong pharmacodynamic effects and efficacy in mouse tumor models. Its anti-tumor efficacy was enhanced when combined with programmed cell death protein 1 (PD-1) or cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) checkpoint inhibitors. ANV419 also enhances the NK cell killing capacity and increases tumor growth inhibition when used alongside trastuzumab in a Her-2+ xenograft mouse model. In cynomolgus monkeys, the estimated half-life of ANV419 is 24 h, and doses that induced sustained expansion of effector cells were well tolerated without the severe toxicities typically observed with high-dose IL-2. These data support the clinical development of ANV419 in solid tumors and hematological malignancies as monotherapy and in combination with checkpoint inhibitors or agents that induce antibody-dependent cellular cytotoxicity. ANV419 is currently in Phase 1/2 clinical development and may provide cancer patients with a wider therapeutic window than aldesleukin.